CAD/CAM education in dental medicine courses of Portugal and Spain - Marques, Marina (2021)
Aim: to analyse how CAD/CAM technology is included in the dental education curricula of dental schools in Portugal and Spain. Methods: a survey was distributed by e-mail to all Professors of Prosthodontics in Higher Education Institutions of Dental Medicine in the Iberian Peninsula. Response rate was 48% (total: 12 institutions). Results: CAD/CAM technology is covered in the training of future Dentists in the Iberian Peninsula, although at a reduced level. Most of students have access to CAD/CAM systems, within the Institution. However, in Portugal it is used only in specific situations, while in Spain it is used more routinely. The most common CAD/CAM materials used in Portugal are lithium disilicate, zirconia and metals. In Spain, it is also used alumina, leucite, feldspathic ceramics and composites for indirect restorations. Although CAD/CAM technology is taught in different graduation levels in Dentistry, it is considered that Portuguese and Spanish graduation level students are not able to use it without additional training. In a post-graduation level, there is a difference between students in both countries.